In‐School Work Experience and the Returns to Schooling - Light, Audrey (Journal of Labor Economics, 2001)
Students often accumulate substantial work experience before leaving school. Because conventional earnings functions do not control for in‐school work experience, their estimates of the return to schooling include the benefit of work experience gained along the way. Using data from the National Longitudinal Survey of Youth, I estimate wage models with and without controls for in‐school work experience. The estimated schooling coefficients are 25%–44% higher (depending on how I control for ability bias) when in‐school work experience is omitted than when it is included. These findings indicate that conventional models significantly overstate the wage effects of “school only.”